(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
For organic horticulturists, weeds are one of the most difficult, time consuming, or costly production concerns. As the consequence of the organic agriculture has grown, so has the demand for innovative bio pesticides to control weeds. Pathogens, organic chemicals, and natural fiber extracts might all be employed to develop viable bio herbicides. Pathogenic fungus and bacteria are two of the most common microorganisms that might be used as bioherbicides. Herbicidal properties have been proven in byproducts from natural source like as dry distiller’s grain with soluble, corns gluten meals or mustard seeds meal. Bioherbicide potential has also been discovered in essential oil extracts. When applying a bioherbicide, the most important factor to consider is its efficacy, which may be impacted by a variety of factors such as humidity and moisture, application technique, bioherbicide spectrum, and formulation type. Aside from efficacy, bioherbicide use is limited due to cost and concerns about potential human health risks. Because incorporating advanced bioherbicide techniques into existing weed-control offerings could help manage herbicide, lower costs, but also increase crop yields, future research should focus on developing more cost-effective but still effective bioherbicides for weed control, as well as optimizing manufacturing techniques rather than traditions through the use of application submission bioherbicides.